Pensions and hotels at the tourist and sports trails of the Giant Mountains - Wojtas-Harań, Anna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
A characteristic feature of the first guesthouses and hotels in the towns located in the Giant Mountains was their location in close connection with nature. Usually, the developments from the turn of the 20th century freely blended in with a green space amongst immeasurable mountain landscape or a romantic park layout as well as sports and recreation areas. Sports venues such as toboggan runs, bobsleigh runs, ski jumping hills, ski lifts, ski runs, tennis courts, swimming pools and ice rinks were situated in a way giving the impression of a compositional and functional whole with villas and guesthouses. They were placed within larger green spaces with a wide view of the Giant Mountains range from one side or the Jizera Mountains on the other, in direct contact with forest nature and fresh air. The tourist and residential developments were supposed to be an elegant background for sporting events with the mutual use of all natural values of the landscape. Over time, a change in the needs and expectations of tourists and athletes resulted in the fact that some sports areas lost their original purpose or were re-developed. In this situation, guesthouses and hotels lost their attractive neighbourhood. Apart from many other reasons, the harmony between developed areas and open, green areas was disturbed.